2014
DOI: 10.1002/cphc.201402657
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insights into the Charge Relaying Properties of β‐Turn Peptides in Protein Charge Transfers

Abstract: Density functional theory calculations suggest that β-turn peptide segments can act as a novel dual-relay elements to facilitate long-range charge hopping transport in proteins, with the N terminus relaying electron hopping transfer and the C terminus relaying hole hopping migration. The electron- or hole-binding ability of such a β-turn is subject to the conformations of oligopeptides and lengths of its linking strands. On the one hand, strand extension at the C-terminal end of a β-turn considerably enhances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Like the 53 SGGS 56 motif, 53 TGGT 56 in COVA2-39 takes part in a type I b-turn along with V H Y52, which is the first residue (i) in the turn (YTGG). The partial positive dipole from the aligned, up-pointing amides on one face of the b-turn (Sheridan and Allen, 1980;Zhang et al, 2015) forms an electrostatic interaction with the side-chain carboxyl of RBD E484. In addition, V H R71 hydrogen bonds to the 53 TGGT 56 motif and may have a role in stabilizing the interaction between the 53 TGGT 56 motif and RBD E484 (Figure 3D).…”
Section: Both Binding Modes Involve Similar Motifsmentioning
confidence: 99%
“…Like the 53 SGGS 56 motif, 53 TGGT 56 in COVA2-39 takes part in a type I b-turn along with V H Y52, which is the first residue (i) in the turn (YTGG). The partial positive dipole from the aligned, up-pointing amides on one face of the b-turn (Sheridan and Allen, 1980;Zhang et al, 2015) forms an electrostatic interaction with the side-chain carboxyl of RBD E484. In addition, V H R71 hydrogen bonds to the 53 TGGT 56 motif and may have a role in stabilizing the interaction between the 53 TGGT 56 motif and RBD E484 (Figure 3D).…”
Section: Both Binding Modes Involve Similar Motifsmentioning
confidence: 99%
“…The efficiency of the first group to serve as stepping stones is due to their low oxidation or reduction potentials, respectively. Methionine on the other hand can only serve as a hole stepping stone if the oxidized sulfur lone pair is stabilized by a nearby aromatic or amide moiety. It was also shown that, even in the absence of the above-mentioned side groups, the backbones of α- and 3 10 -helices or β-turns can serve as relay stations. In the case of these structures, a large dipole moment decreases the oxidation potential especially at the C-termini of such structures. , …”
Section: Introductionmentioning
confidence: 99%
“…Figure27 The schematic plot of dual relay function of β-turn peptide (a) and the dynamics changes of relevant properties (b)[95,96] (color online).…”
mentioning
confidence: 99%